Cytokeratins in gastroenterology. Systematic review - Pastuszak, Marek; Groszewski, Krzysztof; Pastuszak, Małgorzata; Dyrla, Przemysław; Wojtuń, Stanisław; Gil, Jerzy (Gastroenterology Review/Przegląd Gastroenterologiczny, 2015)
Keratins are proteins that form intermediate filaments of epithelial cell cytoskeleton. The utility of keratin expression determination is based on the fact that epithelial cells acquire a specific pattern of keratin expression during differentiation and maturation, which reflects the specificity of the tissue and the degree of maturation, and generally remains stable during carcinogenesis. Determination of the pattern makes it possible to identify the origin of cells in diagnosing neoplastic lesions as well as in research on pathophysiology or the possibility to apply keratin-positive cell detection in the process of cancer staging and treatment planning. As keratins undergo degradation during apoptosis as caspase substrate the identification of the caspase-derived K18 fragment by the use of specific monoclonal antibody allows us to estimate the apoptosis/necrosis ratio, especially in liver pathology, e.g. nonalcoholic steatohepatitis, chronic hepatitis or graft- versus -host disease or in assessing response to antiviral or antitumour therapy.